Can environmental regulation stimulate the regional Porter effect? Double test from quasi-experiment and dynamic panel data models. (10th September 2021) - Nie, Xin; Wu, Jianxian; Chen, Zhoupeng; Zhang, Anlu; Wang, Han
Abstract: Promoting environmental regulation and the reduction of carbon emissions is of great significance for sustainable development. China plans to achieve the following two major goals by 2030: to experience the peak of carbon dioxide emissions, and to be at the forefront of innovative countries in the world. The realization of these goals not only depends on the environmental regulation policy regarding carbon emissions, but also on the development imbalance among Chinese provinces. The Porter hypothesis theory holds that environmental regulation can produce the Porter effect and promote enterprise innovation; but few studies focused on the causal relationship between environmental regulation and the regional Porter effect. Under this framework, this paper uses propensity score matching - difference in difference (PSM-DID) to construct a quasi-experiment on China's carbon emissions trading pilot policy. Dynamic panel data models are used to double test whether environmental regulation can stimulate the regional Porter effect. The empirical results show that: (1) Under the premise of multiple robustness tests (whether quasi-experimental or dynamic panel data models), no evidence was found in support that environmental regulation can stimulate the regional Porter effect. (2) The reason why the regional Porter effect does not been stimulated is that the pollution heaven effect, induced by the carbon emissions trading pilot policy, counteracts the Porter effect to a certain extent. (3) There is no non-linear relationship between environmental regulation and the regional Porter effect. (4) The analysis of spatial heterogeneity shows that environmental regulation cannot stimulate the Porter effect in the eastern, central, and western regions of China. This suggests that it is very important to establish appropriate provincial environmental regulation objectives and to conduct appropriate environmental regulation in combination with local resource endowments. This study provides quantitative evidence toward an in-depth understanding of the relationship between environmental regulation and the regional Porter effect as represented by the pilot policy of carbon emissions trading. A certain degree of reference is provided for the practice of environmental regulation in other developing countries. Highlights: Environmental regulation cannot stimulate the regional Porter effect. The pollution heaven effect explains why regional Porter effect is not stimulated. No nonlinearity exists between environmental regulation and regional Porter effect. Environmental regulation cannot stimulate the Porter effect in all Chinese regions. The government should appropriately strengthen environmental regulation.